Analisis Semiotika dalam Tradisi Mangupa Pasca Keadaan Duka pada Suku Mandailing - Nurul Hidayah Nasution (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the symbols in the Mangupa tradition during the mourning period of the Mandailing tribe. The findings from this research are symbols in the Mangupa tradition after the Mandailing tribe's mourning period which were analyzed using Charles Sanders Pierce's semiotic theory. The aim of this research is to analyze descriptions of the meaning of symbols in the Mangupa tradition after mourning. The method used in this research is a descriptive qualitative method. Data collection was carried out by means of observation, interviews and documentation. This research was conducted in the library of the Faculty of Languages and Arts, Medan State University. The findings of this research are various symbols in the Mangupa tradition after mourning, namely as follows: (1) Indahan, (2) Pira Ni Manuk, (3) Manuk, (4) Aek Minum, (5) Sira, (6) Sipade , (7) Bulung Ujumg Pisang, and (8) Anduri.